ANALISIS FINANSIAL USAHA BUDIDAYA RUMPUT LAUT DENGAN METODE LONGLINE DI DESA KALIUDA KECAMATAN PAHUNGA LODU KABUPATEN SUMBA TIMUR - H. K. Marak; Sunadji Sunadji; Chaterina A. Paulus (Nusa Cendana University, 2018)
Abstract - This study aims to determine the feasibility of seaweed cultivation with longline method in Kaliuda village, Subdistrictof PahungaLodu, East Sumba Regency.This research used interview method.Determination of the population in this study is the coastal communities who settled in the village Kaliuda work as farmers seaweed cultivation. The samples using proportional random sampling method by taking a sample of 20% of the total target population comprised 156 farmers cultivating seaweed by the longline method. Thus, the number of farmers are taken to be the respondent as many as 30 people.In this study using business analysis. Business analysis method consists of business income analysis, Benefit Cost Ratio (R/C) Analysis, Break Event Point Analysis (BEP), Payback Period (PP) Analysis. These results indicated that the cultivation of seaweed with longline methods in the village Kaliuda experiencing gains and deserves to be continued as a business.Revenue (TR) 8.427.333IDR/ year, total cost (TC) 5.125.200IDR/year has a profit of 3.302.133 IDR. Analysis of Benefit Cost Ratio (R/C) 2, Break Event Point Analysis (BEP) 512.5 kg and (BEP) 10,000IDR, Payback Period (PP) Analysis 1,6. Keywords: Financial, aquaculture, seaweed, Eucheuma cottonii, longline